Managing Forest Conflicts: Perspectives of Indonesia's Forest Management Unit Directors - Fisher, Larry A.; Kim, Yeon-Su; Latifah, Sitti; Mukarom, Madani (Forestry Faculty, Universitas Hasanuddin, 2017)
Recent expansion of the forestry and plantation sectors in Indonesia has intensified agrarian and natural resource conflicts, and created increased awareness of the social, economic and environmental impacts of these disputes. Addressing these disputes is a critical issue in advancing Indonesia's commitment to sustainable forest management. The Forest Management Units (Kesatuan Pengelolaan Hutan, or KPH), have become the pivotal structural element for managing all state forests at the local level, with responsibility for conventional forest management and policy implementation (establishing management boundaries, conducting forest inventory, and developing forest management plans), as well as the legal mandate to communicate and work with indigenous people and local communities. This paper presents the results of a national survey of all currently functioning KPH units, the first of its kind ever conducted with KPH leadership, to obtain a system-wide perspective of the KPHs? role, mandate, and capacity for serving as effective intermediaries in managing forest conflicts in Indonesia. The survey results show that the KPHs are still in a very initial stage of development, and are struggling with a complex and rapidly evolving policy and institutional framework. The most common conflicts noted by respondents included forest encroachment, tenure disputes, boundary conflicts, and illegal logging and land clearing. KPH leadership views conflict resolution as among their primary duties and functions, and underscored the importance of more proactive and collaborative approaches for addressing conflict, many seeing themselves as capable facilitators and mediators. Overall, these results juxtapose a generally constructive view by KPH leadership over their role and responsibility in addressing forest management conflicts, with an extremely challenging social, institutional, and political setting. The KPHs can certainly play an important role as local intermediaries, and in some cases, as facilitative mediators in resolving local conflicts, but only with a more concerted effort from central and provincial government authorities to provide greater consistency in policies and regulations, improved policy communication, and a sustained commitment to strengthening the capacity of individual KPHs.